Porous and highly responsive polymeric fabricated nanometrices for solubility enhancement of acyclovir; characterization and toxicological evaluation - Umar, Ayesha; Barkat, Kashif; Hussain Shah, Syed Nisar; Ashraf, Muhammad Umer; Badshah, Syed Faisal; Ali, Akhtar; Anjum, Irfan; Bin Jardan, Yousef A.; Nafidi, Hiba-Allah; Dauelbait, Musaab; Bourhia, Mohammed (Frontiers in Materials, 2023)
Solubility is one of the major factors which affects several therapeutic mioeties in terms of their therapeutic efficacy. In the current study, we presented a porous and amorphous nanometrices system for the enhancement of the solubility of acyclovir. The polymeric network was fabricated by crosslinking polyethylene glycol-6000, polycaprolactone, and β-cyclodextrin with methacrylic acid by optimizing free radical polymerization technique using methylene bisacrylamide as a crosslinking agent. The formulated nanometrices were then characterized by zetasizer, FTIR, PXRD, SEM, TGA, swelling, sol-gel fraction, drug loading, stability, solubility, and in-vitro dissolution analysis. Since the formulated system has to be administered orally, therefore to determine the in-vivo biocompatibility, nanometrices were administered orally to experimental animals. SEM images provided a rough and porous structure while PXRD showed an amorphous diffractogram of the unloaded and loaded nanometrices. Moreover, the particle size of the optimum loaded formulation was 25 nm higher than unloaded nanometrices due to the repulsion of the loaded drug. A significant loading of the drug with enhanced solubility and dissolution profiles was observed for the poorly soluble drug. The dissolution profile was quite satisfactory as compared to the marketed brand of drug which depicted that the solubility of the drug has been enhanced. Toxicity study conducted on rabbits confirmed the biocompatibility of the nanometrices. The systematic method of preparation, enhanced solubility and high dissolution profile of the formulated nanometrices may be proved as a promising technique to enhance the solubility of poorly aqueous soluble therapeutic agents.